Rome: Economic Change in the 2nd Century BC - The Context of Mosaic as a Luxury Product - Filipe CARMO (Journal of Mosaic Research, 2017)
To understand the Roman economy in the 2nd century BC is something that is not possible without being aware of the process of how the Mediterranean World fused into a political whole, first under the influence and later under the rule of the Roman State. Constructing the economic history of this period is not possible without considering the globalisation that occurred in the Mediterranean political realm, as well as the major changes in the social and economic spheres taking place in the Italian Peninsula. This context makes it possible to lay down a relationship between the conquering process and the changes that came about in the field of the land property and land cultivation. A second relationship may be established between the deep changes that occurred in the distribution of urban and rural populations and the consumption structure, the origin of corn supplies and the changes in the economic tissue in general. Further consideration is given to the economic significance of the proceeds coming from the war along with the revenues that Roman ruling officials and economic agents obtained while administering the imperial domain. The appetite for luxury goods that resulted from this process led in particular to the building of wealthy houses where fine mosaic pavements tended to be a common feature.